PRONUNCIATION PROBLEMS IN PRESCHOOL CHILDREN - A.J. Tajimuratov; Gulzada Jumamuratova (International Journal of Literature and Language Studies, 2026)
This article investigates the prevalent pronunciation difficulties observed in preschool children learning English. It examines typical phonological errors, such as substitution, omission, distortion, and addition, which often impede clear communication. Potential contributing factors, including developmental stage, exposure to language, and auditory processing skills, are discussed.